2010
DOI: 10.1254/jphs.09267fp
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Calcium Exchangers in Rat Ameloblasts

Abstract: Abstract. Although the central role of ameloblasts in synthesis and resorption of enamel matrix proteins during amelogenesis is well documented, the Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 29 publications
(21 reference statements)
6
59
0
1
Order By: Relevance
“…Surprisingly, only one patch-clamp study of ameloblasts has been reported in the literature and that was solely to investigate the properties of the electrogenic Na þ -Ca 2þ exchanger in rat ameloblasts [30]. Our present knowledge predicts the presence of ion channels for Cl À and K þ , and it is quite probable that Ca 2þ channels are involved in Ca 2þ entry into the cells at the basolateral membrane.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 74%
See 1 more Smart Citation
“…Surprisingly, only one patch-clamp study of ameloblasts has been reported in the literature and that was solely to investigate the properties of the electrogenic Na þ -Ca 2þ exchanger in rat ameloblasts [30]. Our present knowledge predicts the presence of ion channels for Cl À and K þ , and it is quite probable that Ca 2þ channels are involved in Ca 2þ entry into the cells at the basolateral membrane.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 74%
“…Calcium transport across the ameloblast layer is thought to involve the exchange of intracellular Ca 2þ with extracellular Na þ at the apical membrane [30e32]. The "classic" NCX Na þ -Ca 2þ exchangers have been identified not only by expressional profiling but also by patch-clamp electrophysiology [30]. There is also strong histochemical evidence for the expression of the more recently discovered potassium-dependent sodium/calcium exchanger NCKX4 (also termed as SLC24A4) in maturation ameloblasts [32] but no functional data are available at the moment.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 99%
“…These include Plasma Membrane Ca 2+ ATP-ases (PMCA) [1719], the Na + /Ca 2+ exchangers NCX1 and NCX3 [20, 21] and NCKX4 [1315]. Compared to the plasma membrane ATPases and NCX1/ NCX3 that are expressed in secretory stage and continued expression at the same (NCX1) or reduced (NCX3) level at maturation stage [21], the expression of NCKX4 starts at late secretion and rapidly increases at maturation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the plasma membrane ATPases and NCX1/ NCX3 that are expressed in secretory stage and continued expression at the same (NCX1) or reduced (NCX3) level at maturation stage [21], the expression of NCKX4 starts at late secretion and rapidly increases at maturation stage. NCKX4 also has a transport capacity much higher than PMCA and NCX’s [20]. Null mutation of Nckx4 severely reduces enamel mineralization at maturation stage [13].…”
Section: Discussionmentioning
confidence: 99%
“…Na ϩ /Ca 2ϩ exchangers belong to either the SLC8A 2 gene family of K ϩ -independent Na ϩ /Ca 2ϩ exchangers, encoding three distinct NCX1-3 proteins (7), or the SLC24A gene family of K ϩ -dependent Na ϩ / Ca 2ϩ exchangers encoding the five distinct NCKX1-5 proteins (8). Transcripts of both NCXs and NCKXs were expressed at different stages of the developing enamel (9,10), specifically NCX1, NCX3, and NCKX4. Moreover, the highest SLC24A4 gene (accession number AF520705) transcript levels were observed in maturation-stage ameloblasts and the NCKX4 protein was localized at the apical pole suggesting that NCKX4 is a key Ca 2ϩ transporter during amelogenesis (10).…”
mentioning
confidence: 99%